CITIZEN JOURNALISM SEBAGAI MEDIA PARTISIPASI PEMBANGUNAN AKUNTABILITAS PEMERINTAH - Hastjarjo, Sri (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
One of the indicators of a democratic governance is the opportunity fo its citizen to participate in the governmnental processes, from the planning, implementation, and controling/evaluation stages. One of the important aspect is the accountability of the government to its citizenâwhich require a two-way street or reciprocal information transparency. The development of citizen journalismâfacilitated by the communication and informaston technology (especfially online media and social media) has enabled citizen to practice journalism activities to report the public issues which are uncovered by the mainstream mass media. This research was an action research, using qualitative approaches at the Regency of Karanganyar and the City of Surakarta. The data were collected using interviews, FGDs, and observation techniques, involving NGOâs activist in the area of public policy. This research finds that citizen journalism has a potential to be used as a monitoring mechanism on the govermental processes and as a media to diseminate the monitoring results in the reports that comply to the journalism principlesâwhich in turn will help in developing the government accountability.